Performance Variable: Influenced by Training, Organizational Culture, and Motivation - Budiono, Aris; Husen, Achmad; Suparno , Suparno (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study investigates the impact of training, organizational culture, and motivation on employee performance in a service company, focusing on both their direct and indirect relationships and strategies for improvement. The research utilizes a quantitative survey and multiple linear regression analysis. Research methodology: This research seeks to examine the influence of training, organizational culture, and motivation on employee performance within a service company. This study also examines the direct and indirect relationship between these variables in improving employee performance. Results: The study results indicate that training, organizational culture, and motivation significantly affect employee performance, both simultaneously and partially. Conclusions: Investing is not as complicated as it may seem, and with careful planning, housewives can easily contribute to their family's financial well-being through strategic investment choices. Limitations: The F test shows that the regression model meets the model suitability criteria, and simultaneously, the three independent variables affect the dependent variable, partially revealing that organizational culture and motivation affect Performance, but training does not. Contribution: This study contributes to the understanding of how training, organizational culture, and motivation interact to influence employee performance in service companies. It offers practical insights for HR practitioners and management by highlighting that while motivation and culture have a strong direct effect, training alone may require enhancement in design or delivery to be impactful. The findings also support the development of more integrated employee development programs that align organizational values with personal incentives to improve performance outcomes.